Cover Picture: Thermal and Photolytic Transformation of NHC–B, N‐Heterocycles: Controlled Generation of Blue Fluorescent 1, 3‐Azaborinine Derivatives and 1H‐Imidazo[1, 2‐a]indoles by External Stimuli (Chem. Eur. J. 40/2015). Issue 40 (16th September 2015) - McDonald, Sean M.; Mellerup, Soren K.; Peng, Jinbao; Yang, Dengtao; Li, Quan‐Song; Wang, Suning
Abstract : The unusual and distinct pathways . of molecular transformation by N‐heterocyclic carbene‐bound B, N‐heterocycles are depicted in the cover image. S. Wang and co‐ workers show in their Full Paper onpage 13961 ff. that NHC‐B, N‐heterocycles can act as a common precursor for rare 1, 3‐azaborinine derivatives and imidazo[1, 2‐a]indoles. The transformation of NHC‐B, N‐heterocycles to these two classes of molecules can be controlled with high selectivity by using light or heat. With light, the B, N‐heterocycle transforms to a 1, 3‐azaborinine derivative, whereas with heat, it generates an imidazo[1, 2‐a]indole quantitatively. The cover art was designed and produced by Yufei Li, a Ph.D. student in S. Wang's laboratory.